2021
DOI: 10.31234/osf.io/d3mj7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reading skill correlates in frontal cortex during semantic and phonological processing

Abstract: Previous studies have generally shown that reading skill is related to a left hemisphere network involving temporal, parietal, or frontal components. A limitation of many of these studies, however, is the neuroimaging of a single reading task, so we know less about how skill modulates the engagement of reading network during various reading tasks. Within the connectionist model, reading engages both phonological and semantic processing regardless of whether it is for pronunciation or meaning. Both target [i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
(127 reference statements)
1
2
0
Order By: Relevance
“…In 7-year-old children, stronger functional connectivity from dorsal IFG to STG during phonological processing has been shown to predict better word reading skills later in development ( Wang et al, 2021a ). A recent study using the same word rhyming and meaning tasks as the current study found that better readers showed greater engagement of the dorsal IFG (pars opercularis) during phonological processing and greater engagement of the ventral IFG (pars triangularis) during semantic processing ( Brozdowski and Booth, 2021 , preprint ). However, this study focused on single word reading and did not examine connectivity.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In 7-year-old children, stronger functional connectivity from dorsal IFG to STG during phonological processing has been shown to predict better word reading skills later in development ( Wang et al, 2021a ). A recent study using the same word rhyming and meaning tasks as the current study found that better readers showed greater engagement of the dorsal IFG (pars opercularis) during phonological processing and greater engagement of the ventral IFG (pars triangularis) during semantic processing ( Brozdowski and Booth, 2021 , preprint ). However, this study focused on single word reading and did not examine connectivity.…”
Section: Discussionsupporting
confidence: 51%
“…In a recent study using a word rhyming and a word meaning task, better readers showed greater engagement of the dorsal IFG (pars opercularis) during phonological processing ( r = 0.40) and a trend for greater engagement of the ventral IFG (pars triangularis) during semantic processing ( r = 0.30; Brozdowski and Booth, 2021 , preprint ). However, reading skill was only assessed at the single-word level.…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, we found TMS-induced changes in fine-grained multi-voxel activity patterns in the left IFC between effective and sham TMS, selectively for pseudoword (but not for word) reading. In terms of the functional role of the left IFC for reading, theories hold that it is crucial for phonological output resolution and rhyming during reading (Taylor et al, 2013; Brozdowski & Booth, 2021), as well as attention and working memory (Corbetta et al, 2002; Tops & Boksem, 2011). With pseudowords having a higher decoding demand and thus requiring more effort, specifically after inhibition of the left TPC, it is likely that differences in response patterns of the left IFC at least partially stem from higher demands on attention, executive functions, and cognitive control.…”
Section: Discussionmentioning
confidence: 99%